Education in the teaching context of the Amazon scenario (Research, Society and Development, 2023)
This study addresses Inclusive Special Education, an educational modality that seeks the inclusion of students with special needs, preferably in regular education, from Early Childhood Education to Higher Education. The study also highlights the challenges faced by teachers in the inclusive classroom, highlighting the importance of new teaching approaches and a different perspective when working in this context. Brazilian legislation, such as the National Education Guidelines and Bases Law, has been crucial to advancing inclusive education. However, studies point to setbacks in previous years, but highlight the return of inclusion policies with the new government management in 2023. The objective of this study is to debate the education of deaf people and the inclusion of hearing people in the school context, with a focus on effective inclusion of Libras in public schools in Manaus. The research methodology involved a qualitative and bibliographic approach, including classroom observations. The data was collected from the Municipal Department of Education and Libras teachers. The research was conducted in the Municipality of Manaus, Amazonas, where the need for greater qualification of professionals in Libras was observed to guarantee the effective inclusion of deaf students. The research concludes that there are still challenges to be overcome in inclusive education in Manaus, especially in the training of professionals in Libras. The inclusion of hearing people in regular schools, with Libras teaching, is seen as a way of promoting full interaction between deaf and hearing students, contributing to a more fair and egalitarian society.